Calendario de ganadería (rodeo de cría) en ambientes áridos y semiáridos - Tessi, José María; Avila, Roxana Edith; Brunello, Gabriela Esther; Paz, Juan Mariano (Estación Experimental Agropecuaria La Rioja, INTA, 2023)
EEA La Rioja